Spinal block and delirium in oncologic patients after laparoscopic surgery in the Trendelenburg position: A randomized controlled trial. - Jorge Kiyoshi Mitsunaga; Vinicius Fernando Calsavara; Elton Shinji Onari; Vinicius Monteiro Arantes; Carolina Paiva Akamine; Adriana Mayumi Handa; Michael Madeira de la Cruz Quezada; Franco Yasuhiro Ito; Ana Carolina Souza Porto; Eduardo Henrique Giroud Joaquim; Giane Nakamura (PLoS ONE, 2021)
Delirium is the most common postsurgical neurological complication and has a variable incidence rate. Laparoscopic surgery, when associated with the Trendelenburg position, can cause innumerable physiological changes and increase the risk of neurocognitive changes. The association of general anesthesia with a spinal block allows the use of lower doses of anesthetic agents for anesthesia maintenance and facilitates better control over postoperative pain. Our primary outcome was to assess whether a spinal block influences the incidence of delirium in oncologic patients following laparoscopic surgery in the Trendelenburg position. Our secondary outcome was to analyze whether there were other associated factors. A total of 150 oncologic patients who underwent elective laparoscopic surgeries in the Trendelenburg position were included in this randomized controlled trial. The patients were randomized into 2 groups: the general anesthesia group and the general anesthesia plus spinal block group. Patients were immediately evaluated during the postoperative period and monitored until they were discharged, to rule out the presence of delirium. Delirium occurred in 29 patients in total (22.3%) (general anesthesia group: 30.8%; general anesthesia plus spinal block: 13.8% p = 0.035). Patients who received general anesthesia had a higher risk of delirium than patients who received general anesthesia associated with a spinal block (odds ratio = 3.4; 95% confidence interval: 1.2-9.6; p = 0.020). Spinal block was associated with reduced delirium incidence in oncologic patients who underwent elective laparoscopic surgeries in the Trendelenburg position.